Modulus reductions of dam embankment materials based on downhole array time series. Issue 1 (February 2020) - Kishida, Tadahiro; Park, DongSoon; Sousa, Rita L.; Armstrong, Richard; Byon, Young-Ji
A database of three-component acceleration time series recorded at downhole arrays in earthen dam cores was published by the Japan Commission on Large Dams. This study reviews the acceleration time series in nine earthfill and rockfill dams in Japan. The apparent shear wave velocities between downhole sensors in each dam during strong shakes are determined by calculating the wave travel time between the recorded time series. Transient shear strains are calculated from the differences in the displacement time series between sensors through the double integration of filtered acceleration time series. The modulus reduction curves of the in situ core materials are constructed by combining the apparent shear wave velocities and shear strains. The modulus reduction data are then compared with empirical models. Observations show considerable uncertainties and dam-dependent characteristics in the extracted in situ shear modulus. Accordingly, this study proposes a methodology to update the empirical modulus reduction model for dam core materials on the basis of observed data on downhole time series.